PENGARUH KERAGAMAN PRODUK TERHADAP MINAT BELI KONSUMEN PADA CAFE AMIRAH DI SITUBONDO DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Zahroni, Zahroni; Arief, Muhammad Yahya; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing management can be defined as the analysis, planning, implementation and control of programs designed to create, build and maintain profitable exchanges with target markets with a view to achieving organizational goals. The purpose of this study was to analyze and examine the effect of product diversity on consumer buying interest at Cafe Amirah in Situbondo with consumer satisfaction as an intervening variable. The population in this study are consumers of Cafe Amirah, Situbondo Regency. The sampling technique was determined by the simple random sampling method. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that product diversity has a significant effect on consumer satisfaction. Product diversity has a significant effect on consumer buying interest. Consumer satisfaction has a significant effect on consumer buying interest. Product diversity has a significant effect on consumer buying interest through consumer satisfaction.